2019
DOI: 10.1016/j.isci.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Populations Exhibit Differential Dynamic Responses to Increased Energy Demand during Exocytosis In Vivo

Abstract: SummaryMitochondria are dynamic organelles undergoing fission, fusion, and translocation. These processes have been studied in cultured cells; however, little is known about their regulation in cells within tissues in vivo. We applied four-dimensional intravital microscopy to address this in secretory cells of the salivary gland. We found that mitochondria are organized in two populations: one juxtaposed to the basolateral plasma membrane and the other dispersed in the cytosol. Under basal conditions, central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…It is generally well accepted that dividing cells, including cancer cells, meet their energy demands by reprogramming their cell metabolism such as altering mitochondrial dynamics. 37,38 Our data suggested that MCU-mediated mitochondrial Ca 2+ uptake may promote mitochondrial fission and inhibit mitochondrial fusion, which is in agreement with several previous reports. 20,21 Over the past decades, multiple studies have reported that mitochondrial biogenesis and quality control are often upregulated in various types of cancer, including breast cancer, lung cancer, and hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is generally well accepted that dividing cells, including cancer cells, meet their energy demands by reprogramming their cell metabolism such as altering mitochondrial dynamics. 37,38 Our data suggested that MCU-mediated mitochondrial Ca 2+ uptake may promote mitochondrial fission and inhibit mitochondrial fusion, which is in agreement with several previous reports. 20,21 Over the past decades, multiple studies have reported that mitochondrial biogenesis and quality control are often upregulated in various types of cancer, including breast cancer, lung cancer, and hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…An RT-qPCR-based method was employed to measure the relative mtDNA copy number, as previously described. 37 Quantitative reverse transcription PCR (RT-qPCR) analyses Total RNA was isolated from cultured CRC cells or human CRC tissues and reversely transcribed. RT-qPCR was performed as previously described.…”
Section: Knockdown and Overexpression Of Target Genesmentioning
confidence: 99%
“…parasitism or adaptation to freshwater) may be achieved via different evolutionary pathways 99101 and the consequences for energy demands for an organism may be just one of a plethora of factors including thermal tolerance 102 , aerial exposure 103 , sensitivity to salinity 104 , light 105 or metal concentrations 106 . In addition to the regulation of their transcription and translation 107,108 , mitochondria are very dynamic structures often undergoing continuous fusion, fission and motility, events that can potentially affect their bioenergetic capacities 109 . However, the extent of these rearrangements and the cues that trigger them are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bottom right: regional variations in mitochondrial distribution allows for subcellular specification of mitochondrial function. Neurons (left from Gao et al, 2019 ) and salivary acinar cells (right from Porat-Shliom et al, 2019 ) both display regional heterogeneity of mitochondrial networks. All images reproduced with permission.…”
Section: Mitochondrial Network Structurementioning
confidence: 99%
“…Mitochondrial network morphology is not only specific to cell types but also demonstrates intracellular heterogeneity. Within a cell, mitochondria positioned at different site-specific regions display different morphology and biochemical properties ( Romashko et al, 1998 ; Kuznetsov et al, 1998 , 2004a , 2006 ; Collins et al, 2002 ; Collins and Bootman, 2003 ; Glancy et al, 2015 ; Benador et al, 2018 ; Porat-Shliom et al, 2019 ; Willingham et al, 2019 ). For example, mitochondrial populations close to the plasma membrane play an important role in functional coupling of ATP guided ion channels (e.g., Ca 2+ entry) ( Lawrie et al, 1996 ).…”
Section: Mitochondrial Network Structurementioning
confidence: 99%